Proposal for adaptive re-use on pre-war urban schools Case Study: ( former ) St.Mary’s Girls’ School, No.7, Jalan Tengah, Kuala Lumpur / Roslan Salim - Salim, Roslan (1999)
The main purpose of this dissertation is to study the potential development programme for urban pre-war schools, which were to be relocated elsewhere away from urban setting. When such situation happens, these schools will have to be carefully proposed for adaptive re-use so that it benefits everyone, especially both the developers and the local community. The StMary’s Girls’ School, in Jalan Tengah Kuala Lumpur ( within the 'Golden Triangle ‘ ) was recently relocated to Taman Intan Baiduri Kepong Kuala Lumpur due to improper planning strategy and improper design proposal. The buildings are now left unattended and in very poor condition. If no proper development programme is proposed, the buildings will be declared unfit to live and demolition order will follow suit. In this study, the author is therefore involved in finding a suitable new use for the pre-war school buildings, so that on the overall context of the site, preserving the old pre-war buildings will be seen as the catalyst to the overall development into the site. Adaptive re-use of the pre-war buildings and redevelopment of the overall former school site has been seen as the approach to conserve the prewar buildings and enhancement the environment of the site. Based on the location aspects and property market values ( theoretical-practical aspects ), the most suitable new use will be proposed and envisaged.